Retinal Degeneration Associated With RPGRIP1: A Review of Natural History, Mutation Spectrum, and Genotype–Phenotype Correlation in 228 Patients - Beryozkin, Avigail; Aweidah, Hamzah; Carrero Valenzuela, Roque Daniel; Berman, Myriam; Iguzquiza, Oscar; Cremers, Frans P. M.; Khan, Muhammad Imran; Swaroop, Anand; Amer, Radgonde; Khateb, Samer; Ben-Yosef, Tamar; Sharon, Dror; et al. (Frontiers in Cell and Developmental Biology, 2021)
Purpose: RPGRIP1 encodes a ciliary protein expressed in the photoreceptor connecting cilium. Mutations in this gene cause ~5% of Leber congenital amaurosis (LCA) worldwide, but are also associated with cone-rod dystrophy (CRD) and retinitis pigmentosa (RP) phenotypes. Our purpose was to clinically characterize RPGRIP1 patients from our cohort, collect clinical data of additional RPGRIP1 patients reported previously in the literature, identify common clinical features and seek genotype-phenotype correlations. Methods: Clinical data was collected from 16 patients of our cohort and 212 previously reported RPGRIP1 patients and included (when available) family history, best corrected visual acuity (BCVA), refraction, comprehensive ocular examination, optical coherence tomography (OCT) imaging, visual fields (VF) and full-field electroretinography (ffERG). Results: Out of 228 patients, the majority (197, 86%) were diagnosed with LCA, 18 (7%) with RP, and 13 (5%) with CRD. Age of onset was during early childhood (n=133, average of 1.7 years). All patients but 6 had moderate hyperopia (n=59, Mean of 4.8D), and average BCVA was 0.06 Snellen (n=124; only 10 patients had VA>0.10 Snellen). On funduscopy, narrowing of blood vessels was noted early in life. Most patients had mild bone spicule-like pigmentation starting in the midperiphery and later encroaching upon the posterior pole. OCT showed thinning of the outer nuclear layer (ONL), while cystoid changes and edema were relatively rare. VFs were usually very constricted from early-on. ffERG responses were non-detectable in the vast majority of cases. Most of the mutations are predicted to be null (363 alleles) and 93 alleles harbored missense mutations. Missense mutations were identified only in two regions: the RPGR-interacting domain and the C2 domains. Biallelic null mutations are mostly associated with a severe form of the disease whereas biallelic missense mutations usually cause a milder disease (mostly CRD). Conclusions: Our results indicate that RPGRIP1 biallelic mutations usually cause severe retinal degeneration at an early age with a cone>rod pattern. However, most of the patients exhibit preservation of some (usually low) BCVA for a long period of time and can potentially benefit from gene therapy. Missense changes appear only in the conserved domains and are associated with a milder phenotype.